Indications and adverse events of teriparatide: based on FDA adverse event reporting system (FAERS) - Wen, Ming-Tao; Li, Jia-Cheng; Lu, Bo-Wen; Shao, Hua-Rong; Ling, Pei-Xue; Liu, Fei; Li, Gang; Luo, Di (Frontiers in Pharmacology, 2024)
Background: Teriparatide is approved for osteoporosis. Post-marketing surveillance is critical given its widespread use.Objective: To investigate adverse events (AEs) associated with teriparatide using the FAERS database, compare association strengths for key AEs, and explore potential applications to provide clinical reference. Methods: FAERS data from 2004 to 2023 were analyzed. Reports where teriparatide was the primary suspect drug were included. Adverse events were mapped to System Organ Classes and Preferred Terms.Disproportionality analysis using ROR, PRR, BCPNN and EBGM algorithms was conducted to detect safety signals.Results: 107,123 reports of teriparatide as primary suspect drug were analyzed. Key AEs included pain in extremity (PRR:4.54), muscle spasms (PRR:5.11), fractures (PRR range: 17.67-552.95), increased calcium (PRR:50.73) and heart rate (PRR:3.4). Teriparatide exhibited higher strength for increased calcium (PRR:50.73) than fractures ). We identified off-label use in arthritis (0.57%) and cancer (0.12%). For osteoporosis, main AEs were pain (18.2%), fractures (12.4%), muscle spasms (7.7%) and nausea (6.5%), while for glucocorticoid-induced osteoporosis, AEs included fractures (24.1%), pain (13.2%), decreased bone density (9.8%) and nausea (5.1%).Our analysis provides real-world safety data on teriparatide. Findings reveal key AEs, compare association strengths, highlight off-label use, and deliver insights into different indications. Ongoing vigilance and research are critical to guide teriparatide's clinical use.